BINARY OPPOSITION IN THE EXPRESSION OF TABOOS OF THE TOLOTANG COMMUNITY OF OTTING VILLAGE: A LÉVI-STRAUSSIAN ANTHROPOLOGICAL STUDY - Fandi Syukur; Nensilianti Nensilianti; Suarni Syam Saguni (Media Inovasi Pendidikan dan Publikasi, 2026)
This study aims to describe the structure of binary oppositions, mitemes, and myths within the pamali (taboo) expressions of the Tolotang community in Otting Village through the perspective of Lévi-Strauss’s Structural Anthropology. Using a descriptive qualitative method, the researcher analyzes expressions that reflect the collective mindset of the Tolotang community in organizing their social and spiritual realities. The results indicate that pamali expressions operate through six primary categories of binary opposition: healthy vs. sick, lucky vs. unlucky, polite vs. impolite, safe vs. dangerous, clean vs. dirty, and respectful vs. disrespectful. The miteme analysis identifies narrative relations covering aspects of behavior, fate, eating, illness, sleep, and death, which systematically construct myths of illness, fate, and death. These findings confirm that pamali functions as a social control system and a manifestation of a collective logic that maintains stability and harmony between individuals, society, and the spiritual world. The hierarchical social structure of the Tolotang community reinforces adherence to this oral tradition to consistently ensure the continuity of moral values and communal ethics.